THE ASSESSMENT OF SELF-PERCEIVED EDUCATIONAL NEEDS AND COMPETENCY LEVEL OF EMERGENCY NURSES AT TERTIARY CARE HOSPITAL LAHORE - ULLAH , T; SIDDIQUE , H; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Competency in emergency nursing is crucial for ensuring high-quality patient care in fast-paced healthcare environments. Understanding emergency nurses' self-perceived educational needs and skill competencies is essential for guiding future training and improving patient outcomes. Objective: To assess emergency nurses' self-perceived educational needs and skill competencies at a tertiary care hospital in Lahore. Methods: A descriptive cross-sectional study was conducted using convenience sampling. The study population comprised 125 emergency staff nurses. Data were collected using a structured questionnaire and analyzed using descriptive statistics. Frequency distribution and data normality checks were performed to assess the nurses' educational background and skill competencies. Results: Most respondents (71.2%) held an associate diploma in general nursing, 13.6% had a post-RN qualification, and 15.2% held a Generic BSN. Regarding skill competency, 44% of respondents perceived themselves as highly competent, 40.8% as qualified, and 15.2% as least competent, particularly in areas like defibrillation and neurological assessment. Furthermore, 60% of the nurses needed additional education to enhance their patient care skills. Conclusion: The study concluded that emergency nurses at tertiary care hospitals require further education and training to enhance their knowledge and improve patient care outcomes. Continuous professional development programs focusing on skill enhancement are recommended to bridge the identified competency gaps.